Biaxially-oriented polyester film
A biaxially oriented polyester film with controlled surface roughness and high-melting-point particles addresses the issue of protrusions damaging magnetic heads, enhancing the reliability and performance of magnetic recording tapes.
Patent Information
- Application Number
- JP2023122312
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
Magnetic recording tapes with smoother surfaces and thinner designs are prone to damage the magnetic head due to protrusions from hard foreign matter, leading to errors and potential drive damage during repeated use.
A biaxially oriented polyester film with controlled surface roughness and specific particle composition, including inorganic particles with high melting points, is used to prevent damage to the magnetic head by limiting protrusions and ensuring smooth operation.
The film provides excellent electromagnetic conversion characteristics while preventing damage to the magnetic head and reducing error signals, ensuring reliable performance in magnetic recording media.
Smart Images

Figure 2025018529000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polyester film for use as a base film in a magnetic recording medium. [Background technology]
[0002] Films (especially polyester films) are used in a variety of industrial material and packaging material applications due to their excellent mechanical properties, electrical properties, dimensional stability, heat resistance, transparency, chemical resistance, and the like. Their usefulness as a base film for tape-type magnetic recording media used for data storage, i.e., magnetic recording tape, is also well known.
[0003] The magnetic recording tape is generally constructed by providing a rough-surfaced backcoat layer on one side of a biaxially oriented polyester film to improve running performance, and a smooth magnetic layer on the opposite side of the backcoat layer. In the field of magnetic recording media, there is always a demand for higher recording capacity, and in order to achieve even higher capacity, studies have been conducted on improving the dimensional stability of magnetic recording tapes, reducing their thickness, and smoothing the magnetic layer surface.
[0004] In order to increase the capacity, it is known that in order to increase the smoothness of the magnetic layer surface, it is effective not only to design the magnetic layer itself provided on the base film to be smooth, but also to smooth the surface of the base film on which the magnetic layer is provided, for example by reducing the diameter of added particles (for example, Patent Documents 1 to 3). Recording and reproducing signals on a magnetic recording tape is usually performed by running the magnetic recording tape inside a drive and sliding the surface of the magnetic recording tape on which the magnetic layer is provided over a magnetic head, so increasing the surface smoothness on the magnetic layer side narrows the gap (spacing) between the magnetic layer side surface of the magnetic recording tape and the magnetic head, which is effective in improving the electromagnetic conversion characteristics.
[0005] In addition, when the magnetic recording medium is stored in a roll during the manufacturing process, the protrusions formed on the backcoat layer surface are transferred to the magnetic layer surface, forming depressions on the smooth magnetic layer surface, thereby reducing the smoothness of the magnetic layer surface. Therefore, it is known that not only smoothing the magnetic layer surface but also limiting the roughening of the backcoat layer surface is effective for smoothing the magnetic layer surface (for example, Patent Document 4). In addition, when stored in a roll state, as the base film becomes thinner, large particles such as foreign matter contained in the base film and reaggregates of added particles are pushed up onto the smooth surface, generating gentle undulations on the magnetic layer surface, reducing the smoothness of the magnetic layer surface, and eventually generating error signals. In order to prevent this, it is also effective to reduce the amount of foreign matter in the base film. Specifically, a method is used to remove foreign matter using a high-precision filter when extruding molten polymer in the base film manufacturing process (for example, Patent Document 5). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2010-49731 A [Patent Document 2] JP 2010-250910 A [Patent Document 3] JP 2016-192247 A [Patent Document 4] JP 2020-164807 A [Patent Document 5] JP 2021-111431 A Summary of the Invention [Problem to be solved by the invention]
[0007] Even if the surface of the base film is designed using the method described in the aforementioned patent document and measures are taken to remove foreign matter in the base film during the manufacturing process, a problem arises in that the magnetic head may be scratched or damaged during the process of recording and reproducing signals on the magnetic recording tape.
[0008] Nowadays, as the capacity of the magnetic recording tape increases, the magnetic layer surface becomes smoother, narrowing the spacing, and the magnetic recording tape itself becomes thinner and longer, so that foreign particles remaining in the base film are more likely to affect the system. As mentioned above, in the process of recording and reproducing signals on the magnetic recording tape, the magnetic recording tape is repeatedly slid over the magnetic head, so protrusions on the tape surface caused by hard coarse particles contained in the base film come into contact with the magnetic head. Not only do the protrusions cause errors in reading and writing the tape, but if the particles that form the protrusions are hard, they can also damage the material that makes up the magnetic head, and if the tape is reused, it may destroy the drive one after another, so it is necessary to control the amount of foreign particles present.
[0009] In light of these circumstances, the present invention provides a biaxially oriented polyester film for base films of magnetic recording media that does not damage the magnetic head even when repeatedly slid over the magnetic head and that generates fewer error signals in the magnetic recording tape, by setting the number of protrusions formed from particle agglomerates added to the film or hard foreign matter contained in the base film within a specified range. [Means for solving the problem]
[0010] Means of Solving the Problems The present inventors have conducted intensive research in view of the above problems and have found that the above problems can be solved by a film having a specific structure, thereby completing the present invention.
[0011] That is, the present invention which achieves the above object is characterized by the following configurations. (1) A biaxially oriented polyester film for magnetic recording media, on the surface A on which the magnetic layer is formed, has 0 to 1 protrusions per 1000 mm that are greater than 0.5 μm in height from the reference plane as analyzed using a shape analysis laser microscope measurement with inorganic particles having a melting point of 1600° C. or more as nuclei. 2 A biaxially oriented polyester film. The height is measured in the direction perpendicular to the surface, and refers to the distance from a reference plane determined by measurement using a laser microscope, which will be described later. (2) The biaxially oriented polyester film according to (1), wherein the surface A has a surface average roughness SRaA of 0.5 nm or more and 5 nm or less, and the surface B other than the surface A has a surface average roughness SRaB of 5 nm or more and 12 nm or less. (3) The biaxially oriented polyester film according to (1), which is composed of at least two layers, a layer A forming the surface A and a layer B forming the other surface. (4) The biaxially oriented polyester film according to (1), having a total thickness of 3 μm or more and 5 μm or less. (5) The biaxially oriented polyester film according to (1), wherein the polyester constituting the biaxially oriented polyester film is a polymer having polyethylene terephthalate or ethylene-2,6-naphthalenedicarboxylate as a main repeating unit. Effect of the Invention
[0012] The biaxially oriented polyester film of the present invention is a biaxially oriented polyester film that has few protrusions formed by hard foreign matter as nuclei, and when used as a base film for magnetic recording media, particularly magnetic recording tape, it can provide a base film for magnetic recording media that has excellent electromagnetic conversion characteristics, has few errors during reading and writing, and can suppress damage to the magnetic head when repeatedly run inside a drive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The form of the biaxially oriented polyester film for magnetic recording tape of the present invention (hereinafter sometimes simply referred to as the polyester film of the present invention) will be described below.
[0014] First, the polyester film of the present invention is a film used as a base film for magnetic recording tape, and is particularly suitable for use as a base for coated magnetic recording media in which a coating film is formed by drying a coating material (such as a dispersion containing magnetic powder for magnetic recording) applied to the polyester film as a base during the manufacturing process for imparting magnetic properties.
[0015] The polyester used in the present invention may be, for example, a polymer having an acid component such as an aromatic dicarboxylic acid, an alicyclic dicarboxylic acid, or an aliphatic dicarboxylic acid, or a diol component as a constituent unit (polymerization unit).
[0016] Examples of the aromatic dicarboxylic acid component include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Of these, terephthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid are preferably used. Examples of the alicyclic dicarboxylic acid component include cyclohexanedicarboxylic acid. Examples of the aliphatic dicarboxylic acid component include adipic acid, suberic acid, sebacic acid, and dodecanedioic acid. Only one of these acid components may be used, or two or more of them may be used in combination.
[0017] As the diol component, for example, ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2'-bis(4'-β-hydroxyethoxyphenyl)propane, etc. can be used, among which, ethylene glycol, 1,4-butanediol, 1,4-cyclohexanedimethanol, diethylene glycol, etc. can be preferably used, and particularly preferably, ethylene glycol, etc. can be used. Only one of these diol components may be used, or two or more of them may be used in combination.
[0018] The polyester may be copolymerized with monofunctional compounds such as lauryl alcohol and phenyl isocyanate, or with trifunctional compounds such as trimellitic acid, pyromellitic acid, glycerol, pentaerythritol, and 2,4-dioxybenzoic acid, without excessive branching or crosslinking, so long as the polymer is substantially linear. In addition to the acid component and diol component, aromatic hydroxycarboxylic acids such as p-hydroxybenzoic acid, m-hydroxybenzoic acid, and 2,6-hydroxynaphthoic acid, as well as p-aminophenol and p-aminobenzoic acid, may be further copolymerized in small amounts that do not impair the effects of the present invention.
[0019] The copolymerization ratio of polymers can be measured by NMR (nuclear magnetic resonance) or microscopic FT-IR (Fourier transform infrared) methods. This can be investigated using infrared microscopy.
[0020] The polyester to be used preferably has a glass transition temperature of less than 150° C., so that it can be biaxially stretched and can exhibit the effects of the present invention, such as dimensional stability. As the polyester to be used in the present invention, it is preferable to use a polymer having ethylene terephthalate or ethylene-2,6-naphthalenedicarboxylate as the main repeating unit, and it may also be a copolymer or modified product thereof, or a polymer alloy with other thermoplastic resins. The polymer alloy referred to here is a polymer multicomponent system, and may be a block copolymer obtained by copolymerization, or a polymer blend obtained by mixing, etc.
[0021] In particular, the polyester used in the present invention is preferably composed mainly of polyethylene terephthalate, since it is easy to apply a process for increasing the crystallite size and the degree of crystal orientation. Here, the term "main component" refers to a component that accounts for 80% by mass or more of the film composition.
[0022] When the polyethylene terephthalate used in the present invention is used as a polymer alloy, the other thermoplastic resin is preferably a polymer compatible with polyester, such as a polyetherimide resin. More preferred.
[0023] The biaxially oriented polyester film of the present invention is a biaxially oriented laminated polyester film consisting of at least two layers, and includes at least two layers, A and B, which constitute the surface layer, but another layer (X) may be present between A and B. The A, B, and other layers (X) are all layers formed by so-called co-extrusion. A preferred embodiment is a two-layer structure consisting of A and B layers. Another preferred embodiment is a layer structure in which an intermediate layer (C layer) is provided between A and B layers, and C layer does not substantially contain particles. A coating layer may be provided on at least one or both sides, but even in this case, A and B layers are considered to "constitute the surface layer". Furthermore, it is preferable that the thickness of A layer is larger than the thickness of B layer. If the thickness of A layer is larger than the thickness of B layer, it is easy to set the average surface roughness of the A layer surface and the B layer surface to a preferred range, which will be described later. When the biaxially oriented polyester film of the present invention is used as a base film for a magnetic recording medium, it is preferable to provide a magnetic layer on the surface (side A) of the above-mentioned A layer and a backcoat layer on the surface (side B) of the B layer in order to obtain a high-density magnetic recording medium, with side A functioning as a layer responsible for smoothness and side B functioning as a layer responsible for running properties.
[0024] The surface average roughness SRaA of the A side of the present invention is preferably 0.5 nm or more and 5.0 nm or less, more preferably 0.5 nm or more and 3 nm or less. If the surface average roughness SRaA is less than the lower limit, the electromagnetic conversion characteristics are improved, but the running property and winding property during the production of the base film and when made into a magnetic recording medium are likely to be poor, and defects such as wrinkles are likely to occur. If it exceeds the upper limit, the running property and winding property during the production of the base film and magnetic recording medium are improved, but the electromagnetic conversion characteristics are likely to be reduced due to spacing loss caused by the unevenness of the surface.
[0025] In addition, the surface average roughness SRaB of the B side is preferably 5 nm or more and 12 nm or less, more preferably 5 nm or more and 9 nm or less. By setting it in this range, the running property is good, defects during the production of the film or magnetic recording medium are suppressed, and the electromagnetic conversion characteristics of the magnetic recording medium are also likely to deteriorate. If SRaB exceeds the upper limit, when a backcoat layer is provided on the surface to form a magnetic recording medium, the surface morphology is transferred to the magnetic layer side, and the electromagnetic conversion characteristics are likely to deteriorate. If it is below the lower limit, the electromagnetic conversion characteristics are improved, but the running property and winding property are likely to be poor during the production of the base film or when it is formed into a magnetic recording medium, and defects such as wrinkles are likely to occur.
[0026] The surface roughness of the above-mentioned sides A and B can be controlled by incorporating particles into the polyester resin constituting the layer having side A (layer A) and the layer having side B (layer B), and by varying the type, amount added, particle size, stretching ratio during base film production, and heat treatment temperature.
[0027] When particles are contained in the biaxially oriented polyester film of the present invention, the type of particles is not particularly limited, and both inorganic particles and organic particles can be used. Examples of particles that can be preferably applied to the A layer include monodispersed spherical particles and aggregated particles with a primary diameter of 10 to 30 nm. It is preferable to contain inactive particles with an average particle diameter of 300 nm or less in the B layer, and in order to control the above-mentioned surface roughness, it is easy to adjust the surface roughness to the range of the present invention by using two or more types of particles in combination. Specific types of particles include, for example, inorganic particles such as clay, mica, titanium oxide, calcium carbonate, wet silica, dry silica, colloidal silica, calcium phosphate, barium sulfate, alumina silicate, kaolin, talc, montmorillonite, alumina, and zirconia; organic particles containing, as a component, acrylic acids, styrene-based resins, silicone, imide, and the like; core-shell type organic particles; and silica-acrylic composite particles. However, when the added particles aggregate during the production process, they may form large protrusions with high hardness, as described below. Therefore, particles made of a substance with a low melting point are preferred, and at least one type selected from the group consisting of inorganic particles such as spherical silica particles, spherical silicone particles, spherical crosslinked polystyrene particles, and silica-acrylic composite particles are preferred.
[0028] Of the protrusions formed on the surface of layer A of the biaxially oriented polyester film of the present invention, the number of protrusions having a height of 0.5 μm or more and a melting point of 1600° C. or more as the core of the protrusions or particles of foreign matter is 1000 m of tape. 2It is necessary that there be 0 or more and 1 or less per unit area, and 0 is more preferable. Recording and reproducing signals on a magnetic tape are usually performed by running the magnetic recording tape in a drive and sliding the surface of the magnetic tape on which the magnetic layer is provided over the magnetic head. Therefore, the coarse protrusions on the surface of the magnetic layer of the magnetic tape come into contact with the magnetic head, and if the hardness of the protrusions is equal to or greater than that of the magnetic head, they will damage the magnetic head. In other words, if the number of protrusions with a height of 0.5 μm or more and a melting point of the core of 1600°C or more exceeds the above upper limit, if the core constituting the coarse protrusions is harder than the magnetic head, it will also damage the material constituting the magnetic head, causing errors when recording and reproducing signals on the magnetic tape, or the error rate will worsen as the tape is repeatedly run without a drive, leading to damage to the drive itself. Note that the height refers to the direction perpendicular to the surface and means the distance from the reference plane determined by measurement with a laser microscope described below.
[0029] The materials that compose the magnetic head vary depending on the magnetic recording medium, but typical materials are inorganic materials such as alloys such as permalloy, and ceramics such as ferrite and alumina. It is generally known that the hardness and melting point of an inorganic compound correspond to the bonding strength of the chemical bonds of the molecules that compose the material, and not including a material with a high melting point in the base film can be considered the same as not including a substance with high hardness.
[0030] The method for setting the number of protrusions having particles with a melting point of 1600°C or higher as a nucleus within the above range is not particularly limited, but examples include not using materials with a melting point of 1600°C or higher for the particles added to the base film to control the above-mentioned surface roughness, using a filter with high filtration accuracy in the film-forming process by extrusion molding in the base film manufacturing process, and selecting the material of the release material, which is one of the components used in manufacturing the filter.
[0031] Here, the method of selecting the material of the release material when manufacturing the filter described above will be described in detail. As a filter used to remove unmelted matter and contaminants from the heated and melted polyester in the polyester extrusion molding process, a porous metal sintered body made by sintering metal powder or metal fiber at high temperature is preferably used as a filter material, and a spacer that does not react with the sintered metal powder or fiber, i.e., a release material, is used in the manufacturing process.
[0032] The material of the release material can be a sheet made of heat-resistant oxide such as stainless steel metal material, graphite, ceramic, etc., or a fabric made of the fibers of these materials, but when the filter material is sintered, some of the release material may chip or the components contained in the release material may precipitate, and the components of the release material may adhere to the filter material itself as fine particles of several μm or less.In addition, the particles that adhere to the filter material surface in this way are difficult to remove by washing, etc., and when the filter with the particles derived from the release material attached to the filter material surface is used as a polyester film resin filter, the particles flow out little by little from the outlet side of the filter material over a long period of several years and are mixed into the resin that passes through the filter.
[0033] When selecting a release material to set the number of protrusions having particles with a melting point of 1600° C. or more as cores within the above range, the higher the melting point of the material, the better, and it is preferable to use a material with a melting point of 2100° C. or more. Examples of materials with a melting point of 2100° C. or more include niobium, molybdenum, tungsten, and tantalum, but from the viewpoints of availability and cost, molybdenum and tungsten are preferred, and tungsten is most preferred.
[0034] When the biaxially oriented polyester film of the present invention is used as a base film for a magnetic recording medium, the total thickness is preferably 3 μm or more and 5 μm or less. If it exceeds 5 μm, the length of each roll that can be stored in a tape cartridge becomes short, making it difficult to meet the demands for high capacity and miniaturization of the tape. If it is less than 3 μm, it is difficult to stably produce, process, and handle the film. As a method for adjusting the thickness, it is possible to adjust the film thickness after biaxial stretching by adjusting the discharge amount of the screw during melt extrusion of the polymer during the film formation of the biaxially oriented polyester film and controlling the thickness of the unstretched film from the die.
[0035] The method for producing the film of the present invention will be described below using a representative example in which polyethylene terephthalate (PET) is used as the polyester. The present invention is not limited to PET films, and other polymers may be used. For example, when a polyester film is formed using polyethylene-2,6-naphthalenedicarboxylate, which has a high glass transition temperature or melting point, extrusion and stretching may be performed at a temperature higher than the temperatures shown below.
[0036] First, PET pellets are produced. PET is produced by one of the following processes: (1) a process in which terephthalic acid and ethylene glycol are used as raw materials, and low molecular weight PET or oligomers are obtained by a direct esterification reaction, and then a polymer is obtained by a polycondensation reaction using antimony trioxide or a titanium compound as a catalyst, or (2) a process in which dimethyl terephthalate and ethylene glycol are used as raw materials, and low molecular weight PET is obtained by a transesterification reaction, and then a polymer is obtained by a polycondensation reaction using antimony trioxide or a titanium compound as a catalyst.
[0037] In order to incorporate particles into the PET constituting the film, it is preferable to disperse the particles in ethylene glycol in the form of a slurry at a predetermined ratio, and add this ethylene glycol during polymerization. When adding particles, for example, the particles in the water slurry or alcohol slurry obtained during particle synthesis are added without drying once, which improves the dispersibility of the particles. Here, if the particle slurry concentration is 5 mass% or less, it is easy to adjust the surface roughness to the range of the present invention. When the particles to be added are inorganic particles, it is also very effective to add glass beads with a number average particle size of 0.5 to 0.05 mm to the particle-containing slurry adjusted to a specific concentration and stir at 1,000 to 5,000 rpm for 1 to 5 hours.
[0038] Next, it is particularly important to directly mix the water slurry of the particles with PET pellets and knead it into PET using a vented twin-screw kneading extruder so that the particle content is 0.1 to 0.5% by mass to prepare a particle master pellet. As a method for adjusting the particle content, a method is preferred in which the particle master pellet of a specific concentration prepared by the above method is diluted with PET that does not substantially contain particles during film formation to adjust the particle content. This is also particularly important because it leads to a reduction in film breakage due to high-temperature heat fixation. Furthermore, when using two or more types of particle master pellets, it is preferable to use a two-stage kneaded particle master pellet that is melt-kneaded again after blending to a predetermined desired content in advance to improve the dispersibility of the particles, since this reduces film breakage during multi-stage high-temperature stretching.
[0039] In this case, various additives, such as compatibilizers, plasticizers, weathering agents, antioxidants, heat stabilizers, lubricants, antistatic agents, brighteners, colorants, conductive agents, crystal nucleating agents, ultraviolet absorbers, flame retardants, flame retardant assistants, pigments, dyes, and the like, may be added within a range that does not impair the characteristic aspects of the present invention.
[0040] Next, the obtained PET pellets are dried under reduced pressure at 180°C for 3 hours or more, and then fed to a heated extruder under nitrogen gas flow or reduced pressure so as not to reduce the intrinsic viscosity. The extrusion rate is uniformized using a gear pump, and the extrusion is discharged from a slit-shaped die and cooled and solidified on a cast drum to obtain a non-oriented sheet. In order to laminate the film, it is preferable to melt-laminate a plurality of different polymers using two or more extruders and lamination devices. As the lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, and these may be combined arbitrarily. Here, in order to control the number of protrusions with a height of 0.5 μm or more within the range of the present invention, it is important to select a material with a high melting point as the release material used when manufacturing the filter to be used, and the removal accuracy of the filter to be used. The filter to be used is a filter that captures foreign matter of 5 μm or more, more preferably a filter that captures foreign matter of 2 μm or more, and the release material used when manufacturing the filter is made of molybdenum or tungsten, making it easy to control the number of protrusions.
[0041] The unoriented sheet thus obtained is then simultaneously biaxially stretched and then stretched again in the transverse direction.
[0042] First, both ends of the non-oriented sheet are held by multiple clips and introduced into a tenter device, where it is biaxially stretched simultaneously in the MD and TD directions. The stretching temperature varies depending on the type of polymer used, but can be determined based on the glass transition temperature (Tg) of the unstretched film. The temperature is preferably in the range of Tg+5 to Tg+40°C, and more preferably Tg+10°C to Tg+30°C. If the temperature exceeds the above range, film breakage occurs frequently in the tenter device and during subsequent edge cutting, which tends to reduce productivity. The stretch ratio in the MD direction during simultaneous biaxial stretching is preferably 3.3 to 3.6 times, and the stretch ratio in the TD direction is preferably 3.8 to 4.0 times, and stretching is preferably performed for 5 to 7 seconds.
[0043] Next, the film is stretched again in the TD direction (TD stretching 2). The stretching temperature in TD stretching 2 is preferably 185 to 200°C, and the stretch ratio in TD stretching 2 is preferably 1.2 to 2.0 times. At this time, simultaneous biaxial stretching in the MD direction may also be performed within a range of 1.0 to 2.0 times. This stretched film is heat set under tension or while relaxing in the width direction. The heat set temperature is preferably 200 to 230°C, the heat set time is preferably 5 to 10 seconds, and the relaxation rate in the case of relaxation is preferably 0.3 to 2.0%.
[0044] Next, the film is introduced into a cooling zone adjusted to 100° C. to 150° C. and slowly cooled, after which the edge portions held by the clips are cut to obtain a biaxially oriented polyester film.
[0045] As the stretching method, the simultaneous biaxial stretching method as described above is preferable because it is easy to control the number of protrusions and the surface roughness, but it is also possible to implement a sequential biaxial stretching method by employing some ingenuity, such as adopting multi-stage stretching for stretching in the longitudinal and transverse directions. EXAMPLES
[0046] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Various properties were measured by the following methods.
[0047] (1) Total film thickness Sampling was done at three equally spaced locations across the width of the film, and for each sample, cross-sectional observation was performed in 10 different locations under the following conditions. The average thickness [μm] obtained was recorded as the thickness at each location, and the average of the three points was recorded as the film thickness [μm]. Measurement equipment: Transmission electron microscope (TEM) Hitachi H-7100FA Measurement conditions: Acceleration voltage 100 kV Measurement magnification: 10,000 times Sample preparation: Ultrathin sectioning (RuO4 staining) Observation surface: TD-ZD cross section (TD: width direction, ZD: thickness direction) Number of measurements: 3 points per field, 10 fields of view were measured.
[0048] (2) Thickness of B layer Sampling was performed by the method described in (1) above. For each sample, three measurement samples were arbitrarily cut out, three-point measurements were performed for each sample, and the average value of the nine-point data was taken as the B layer thickness [μm] at each position. The boundary was determined from the observation results of the interface based on the contained particles and particle concentration. The measurement conditions are as follows. Measuring device: Transmission electron microscope (TEM), Hitachi H-7100FA type Measurement conditions: Acceleration voltage 100 kV Magnification: The maximum magnification at which the entire layer thickness to be measured fits into the microscope field of view is selected from 200,000 times, 20,000 times, 10,000 times, and 5,000 times. Sample preparation: Ultrathin sectioning method (RuO4 staining) Observation plane: TD-ZD cross-section (TD: width direction, ZD: thickness direction) Number of measurements: For , three points are measured for each of the three samples.
[0049] (3) Content of polymer and particles The polymer is dissolved in an appropriate solvent for dissolving the polymer, and the 1H nuclear NMR (nuclear magnetic resonance) spectrum is measured. The appropriate solvent varies depending on the type of polymer. For example, hexafluoroisopropanol (HFIP) / deuterated chloroform is used.
[0050] In the obtained spectrum, the peak area intensity of the absorption specific to the polymer (for example, the absorption of the aromatic protons of terephthalic acid in the case of PET) is determined, and the molar ratio of the polymer is calculated from the ratio and the number of protons. Further, the mass ratio is calculated from the formula weight corresponding to each unit unit of each polymer. The measurement conditions are, for example, as follows, but this is not limited because they vary depending on the type of polymer. Device: BRUKER DRX-500 manufactured by Bruker Solvent: HFIP / deuterated chloroform Observation frequency: 499.8 MHz Reference: TMS (tetramethylsilane) (0 ppm) Measurement temperature: 30℃ Observation width: 10KHz Data points: 64K Acquisiton time: 4.952 seconds pulse delay time: 3.048 seconds Number of times: 256
[0051] If necessary, composition analysis may be performed using a micro FT-IR method (Fourier transform micro infrared spectroscopy). In this case, the ratio of the peak due to the carbonyl group of the polyester to the peak due to other substances is obtained. In order to convert the peak height ratio to a mass ratio, a calibration curve is created in advance using samples with known mass ratios to obtain the polyester ratio relative to the total amount of polyester and other substances. If necessary, an X-ray microanalyzer may also be used in combination. Regarding the content of inactive particles, a solvent that dissolves the polymer but not the inactive particles was selected, the polymer was dissolved, and the particles were centrifuged to obtain the mass percentage.
[0052] (4) Surface average roughness (SRaA, SRaB) The surface is measured using a three-dimensional micro surface profiler (ET-4000AK manufactured by Kosaka Laboratory) and the average surface roughness SRa is calculated from the obtained surface profile curve in accordance with JIS B0601. The measurement conditions are as follows: X-direction measurement length: 0.5 mm, X-direction feed speed: 0.1 mm / sec Y-direction feed pitch: 5μm, Y-direction line count: 40 Cutoff: 0.25mm Stylus pressure: 0.02mN Height (Z direction) magnification: 50,000 times.
[0053] (5) Average particle size of particles in particle-containing PET pellets A 100 nm thick slice is prepared from any position of the particle-containing PET pellet and observed at a magnification of 10,000 times or more using a transmission electron microscope (TEM, for example Hitachi H-7100FA type). Observation is performed at 100 or more different positions, and the equivalent circle diameter of the particles in each observed field is measured. The number average of the equivalent circle diameters measured in all fields is regarded as the average particle diameter of the inert particles contained in the particle-containing PET pellet.
[0054] (6) Number of protrusions with a height of 0.5 μm or more 100cm 2 Two A-sides of the films were stacked together and pressed together by electrostatic force (applied voltage 5.4 kV), and then Newton's rings with double or more rings were sampled from among the rings that were formed by the interference of light in the gaps that formed between the two films at the locations of the coarse protrusions. The A-side of the samples obtained was observed with a shape analysis laser microscope (Keyence VK-X250). The observation conditions were as follows: a 50x objective lens was used to observe a measurement area of 220 μm × 290 μm. The obtained measurement data is analyzed using a multi-file analysis app (VK-Xseries, manufactured by KEYENCE). If there is any inclination or curvature in the total measurement pixel count of 1024 x 768 pixels per field of view, the surface shape correction function (automatic) is used to make it flat, and then a reference plane is set in the image processing function settings. At this time, the reference plane is a plane found from the measurement data (or the corrected data, if correction has been applied) using the least squares method, and this reference plane is used as the origin of height, and a protrusion with a threshold value (protrusion height) of 0.5 μm is determined to be a protrusion with a height of 0.5 μm or more. This is repeated 50 times, and a measurement is performed over 1000 m. 2 The number of protrusions with a height of 0.5 μm or more per unit area was counted.
[0055] (7) Elemental analysis of core particles of coarse protrusions The polyester on the surface of the coarse protrusions obtained by the inspection described in (6) was removed by low-temperature plasma ashing to expose the particles that were the cores of the coarse protrusions to the surface, which were observed at 1,000x magnification with a scanning electron microscope (SEM) and subjected to elemental analysis by energy dispersive X-ray analysis (EDX). When multiple elements were detected that were presumed to be oxides, compounds, or alloys rather than simple metals, the corresponding substances were identified from the elemental ratios in the measurement results.
[0056] (8) Melting point of the core particles of the coarse protrusions The melting point listed in the Basic Chemistry Handbook, 3rd Revised Edition, compiled by the Chemical Society of Japan, Maruzen Publishing, was taken as the melting point of the core particles of the coarse projections identified by the elemental analysis described in (6).
[0057] (9) Error rate The film slit to a width of 1 m is transported with a tension of 200 N, and one surface of the support is coated with magnetic paint and non-magnetic paint as described below, and then slit to a width of 12.65 mm (1 / 2 inch) to form a pancake. (Hereinafter, "parts" means "parts by mass.") Magnetic layer forming coating liquid Barium ferrite magnetic powder 100 parts (Plate diameter: 20.5nm, plate thickness: 7.6nm, Plate ratio: 2.7, Hc: 191kA / m (≒2,400Oe) Saturation magnetization: 44Am 2 / kg, BET specific surface area: 60m 2 / g) Polyurethane resin 12 parts Mass average molecular weight 10,000 Sulfonic acid functional group 0.5meq / g α-alumina HIT60 (Sumitomo Chemical Co., Ltd.) 8 parts Carbon black #55 (Asahi Carbon Co., Ltd.) Particle size 0.015μm 0.5 parts Stearic acid 0.5 parts Butyl stearate 2 parts Methyl ethyl ketone 180 parts Cyclohexanone 100 parts Coating liquid for forming non-magnetic layer Non-magnetic powder α-iron oxide 85 parts Average major axis length 0.09μm, specific surface area by BET method 50m 2 / g pH 7 DBP oil absorption 27~38ml / 100g Surface treatment layer: Al2O3 8% by mass Carbon black 15 parts "Conductex" (registered trademark) SC-U (manufactured by Columbian Carbon Co., Ltd.) Polyurethane resin UR8200 (manufactured by Toyobo Co., Ltd.) 22 parts Phenylphosphonic acid 3 parts Cyclohexanone 140 parts Methyl ethyl ketone 170 parts Butyl stearate 1 part Stearic Acid 2 parts Methyl ethyl ketone 205 parts Cyclohexanone 135 parts.
[0058] For each of the above coating liquids, each component was kneaded with a kneader. The coating liquid was pumped through a horizontal sand mill containing 1.0 mmφ zirconia beads in an amount that filled 65% of the volume of the dispersion section, and dispersed at 2,000 rpm for 120 minutes (time spent substantially in the dispersion section). 5.0 parts of polyisocyanate were added to the resulting dispersion for the nonmagnetic layer coating, and 2.5 parts were added to the magnetic layer coating, and 3 parts of methyl ethyl ketone were further added. The mixture was filtered using a filter with an average pore size of 1 μm to prepare coating liquids for forming the nonmagnetic layer and the magnetic layer, respectively.
[0059] The obtained coating solution for forming a non-magnetic layer was applied to a polyester film and dried so that the thickness after drying was 0.8 μm, and then the coating solution for forming a magnetic layer was applied so that the thickness after drying was 0.07 μm, and while the magnetic layer was still in a wet state, it was oriented and dried using a cobalt magnet with a magnetic force of 6,000 G (600 mT) and a solenoid with a magnetic force of 6,000 G (600 mT). Then, a backcoat layer (carbon black average particle size: 17 nm 100 parts, calcium carbonate average particle size: 40 nm 80 parts, α-alumina average particle size: 200 nm 5 parts dispersed in polyurethane resin and polyisocyanate) was applied so that the thickness after calendaring was 0.5 μm. Next, a calendaring process was performed with a calendar at a temperature of 90 ° C. and a linear pressure of 300 kg / cm (294 kN / m), and then cured at 65 ° C. for 72 hours. Furthermore, the nonwoven fabric and razor blade were attached to a device having a slit product delivery and take-up device so that they were pressed against the magnetic surface, and the surface of the magnetic layer was cleaned with a tape cleaning device to obtain a magnetic tape.
[0060] The obtained tape roll was slit to a width of 12.65 mm (1 / 2 inch) and assembled into an LTO case to create a data storage cartridge with a magnetic recording tape length of 960 m. This data storage was recorded in an environment of 23°C and 50% RH (recording wavelength 0.55 μm) using an IBM LTO8 drive. The recorded data storage cartridge was stored in an environment of 50°C and 80% RH for 7 days. After storing the cartridge at room temperature for 1 day, the entire length was played back and the error rate of the signal during playback was measured. The error rate was calculated from the error information (number of error bits) output from the drive using the following formula. × is considered to be a failure. Error rate = (number of error bits) / (number of written bits) ○: Error rate is 1.0×10 -5 less than ×: Error rate is 1.0×10 -5 The end.
[0061] (10) Driving durability The evaluation is based on the error rate after running 300 times in an environment of 23°C and 50% RH using an IBM LTO8 drive. The error rate is calculated using the following formula from the error information (number of error bits) output from the drive. × is considered a failure. Error rate = (number of error bits) / (number of written bits) ○: Error rate is 1.0×10 -5 less than ×: Error rate is 1.0×10 -5 or an unreadable track has occurred.
[0062] The following examples are provided to illustrate the present invention. In the examples, polyethylene terephthalate is abbreviated as PET and polyetherimide is abbreviated as PEI.
[0063] (1) Preparation of PET pellets: 194 parts by mass of dimethyl terephthalate and 124 parts by mass of ethylene glycol were charged into an ester exchange reactor, and the contents were heated to 140°C to dissolve. Then, 0.3 parts by mass of magnesium acetate tetrahydrate and 0.05 parts by mass of antimony trioxide were added while stirring the contents, and an ester exchange reaction was carried out while distilling off methanol at 140 to 230°C. Next, 0.5 parts by mass of a 5% by mass ethylene glycol solution of trimethyl phosphate (0.025 parts by mass as trimethyl phosphate) and 0.3 parts by mass of a 5% by mass ethylene glycol solution of sodium dihydrogen phosphate dihydrate (0.015 parts by mass as sodium dihydrogen phosphate dihydrate) were added.
[0064] When the ethylene glycol solution of trimethyl phosphate was added, the temperature of the reaction contents dropped. Therefore, the excess ethylene glycol was distilled off while stirring was continued until the temperature of the reaction contents returned to 230°C. After the temperature of the reaction contents in the transesterification reactor reached 230°C in this way, the reaction contents were transferred to the polymerization reactor.
[0065] After the transition, the reaction system was gradually heated from 230°C to 275°C, and the pressure was lowered to 0.1kPa. The time to reach the final temperature and the final pressure was both 60 minutes. After reaching the final temperature and the final pressure, the reaction was continued for 2 hours (3 hours from the start of polymerization), and the stirring torque of the polymerization apparatus showed a predetermined value (the specific value differs depending on the specifications of the polymerization apparatus, but the value shown by polyethylene terephthalate with an intrinsic viscosity of 0.62 in this polymerization apparatus was set as the predetermined value). The reaction system was then purged with nitrogen and returned to normal pressure to stop the polycondensation reaction, and the mixture was discharged into cold water in the form of strands, which were immediately cut to obtain PET pellets of polyethylene terephthalate with an intrinsic viscosity of 0.62 (raw material-1).
[0066] (2-a) Preparation of particle-containing PET pellets: 90 parts by mass of the above-mentioned PET pellets (raw material-1) and 10 parts by mass of a 10% by mass water slurry of cross-linked polystyrene particles with an average particle size of 0.45 μm (1 part by mass as cross-linked polystyrene particles) were fed into a co-rotating, vented twin-screw kneading extruder heated to 280°C, and the vent hole was kept at a reduced pressure of 1 kPa or less to remove moisture, thereby obtaining particle-containing pellets (raw material-2a) containing 1% by mass of cross-linked polystyrene particles and having an intrinsic viscosity of 0.62.
[0067] (2-b) Preparation of particle-containing PET pellets: 90 parts by mass of the above-mentioned PET pellets (raw material-1) and 10 parts by mass of a 5% by mass water slurry of cross-linked polystyrene particles with an average particle size of 0.30 μm (0.5 parts by mass as cross-linked polystyrene particles) were fed into a vented twin-screw kneading extruder of the same rotation type heated to 280°C, and the vent hole was kept at a reduced pressure of 1 kPa or less to remove moisture, thereby obtaining particle-containing pellets (raw material-2b) containing 0.5% by mass of cross-linked polystyrene particles and having an intrinsic viscosity of 0.62.
[0068] (2-c) Preparation of particle-containing PET pellets: 94 parts by mass of the above-mentioned PET pellets (raw material-1) and 5% by mass of water slurry of colloidal silica particles with an average particle size of 0.060 μm, glass beads with an average particle size of 0.05 mm were added to the same direction rotating type vented twin screw kneading extruder heated to 280°C, and 6 parts by mass (0.3 parts by mass as colloidal silica particles) of the water slurry, which was then stirred at 1,000 rpm for 2 hours and filtered to remove the glass beads, were fed into the same direction rotating type vented twin screw kneading extruder heated to 280°C, and the vent hole was kept at a reduced pressure of 1 kPa or less to remove moisture, thereby obtaining particle-containing pellets (raw material-2d) containing 0.3% by mass of colloidal silica particles and having an intrinsic viscosity of 0.62.
[0069] (3) Preparation of two-component composition (PET / PEI) pellets: The PET pellets (raw material-1) obtained by the above method and pellets of PEI “Ultem” (registered trademark) 1010 manufactured by SABIC Innovative Plastics were fed into a vented twin-screw extruder (manufactured by Japan Steel Works, Ltd., screw diameter 30 mm, screw length / screw diameter = 45.5) of the same rotation type equipped with three kneading paddle kneading sections heated to a temperature of 280 ° C., and the pellets were mixed at a shear rate of 100 sec -1 The mixture was melt-extruded with a residence time of 1 minute to obtain two-component composition pellets containing 50% by mass of PEI. The glass transition temperature of the two-component composition pellets thus produced was 150° C. (raw material-3).
[0070] Example 1 Two extruders E1 and E2 were used, and 29 parts by mass of PET pellets (raw material-1), 4 parts by mass of two-component composition pellets (raw material-3), and 67 parts by mass of pellets containing colloidal silica particles with an average particle size of 0.06 μm (raw material-2c) were fed to extruder E1 heated to 280 ° C. after drying under reduced pressure for 3 hours at 180 ° C. Similarly, 55.1 parts by mass of PET pellets (raw material-1), 4 parts by mass of two-component composition pellets (raw material-3), 3.8 parts by mass of pellets containing cross-linked polystyrene particles with an average particle size of 0.3 μm (raw material-2b), 1.1 parts by mass of pellets containing cross-linked polystyrene particles with an average particle size of 0.45 μm (raw material-2a), and 36 parts by mass of pellets containing colloidal silica particles with an average particle size of 0.06 μm (raw material-2c) were blended as B layer raw materials and fed to extruder E2 heated to 280 ° C. after drying under reduced pressure for 3 hours at 180 ° C. These were melt extruded at 300°C and passed through a fiber sintered stainless steel metal filter with a filtration accuracy capable of capturing foreign matter of 2μm or more, and then these were joined in a T-die so that the B layer side faced the cast drum surface in order to laminate them in two layers, and they were cooled and solidified in close contact while applying a static charge to the cast drum with a surface temperature of 25°C, obtaining a laminated unstretched sheet. At this time, the release material used in the manufacturing process of the fiber sintered stainless steel metal filter used was a mesh sheet made of tungsten. While both ends of this laminated unstretched sheet were held by multiple clips, it was preheated at 100°C in a simultaneous biaxial stretching machine and stretched to 3.5 times in the MD direction and 3.6 times in the TD direction at a stretching temperature of 100°C for 6 seconds. Then, it was stretched in a second stage to 1.2 times in the MD direction and 1.5 times in the TD direction for 6 seconds at 190°C. Then, it was heat-set at 220°C for 8 seconds, cut at the clip-held portion, and wound up to obtain a biaxially oriented polyester film with a thickness of 4.6 μm.
[0071] When the obtained biaxially oriented polyester film was used as a magnetic tape, it did not cause errors due to large protrusions having a nucleus with a melting point of 1600°C or more, and had excellent properties as a magnetic tape, as shown in Table 1.
[0072] Example 2 A biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the release material used in the fabrication process of the fiber-sintered stainless steel metal filter through which the raw material was passed after melt extrusion was a mesh sheet made of molybdenum.
[0073] Comparative Example 1 A biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the release material used in the fabrication process of the fiber-sintered stainless steel metal filter through which the raw material was passed after melt extrusion was a mesh sheet made of SUS304. When the obtained biaxially oriented polyester film was used as a magnetic tape, coarse protrusions were detected, which were composite particles with a core of iron, chromium, manganese, and nickel, and running durability was deteriorated. Each metal detected as the core can be assumed to be an alloy component that makes up SUS304.
[0074] Comparative Example 2 A biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the release material used in the fabrication process of the fiber-sintered stainless steel metal filter through which the raw material was passed after melt extrusion was a ceramic cloth made of alumina and silica. When the obtained biaxially oriented polyester film was used as a magnetic tape, coarse protrusions whose nuclei were silica or alumina particles were detected, and running durability was deteriorated.
[0075] Comparative Example 3 A biaxially oriented polyester film was obtained in the same manner as in Example 1, except that the release material used in the fabrication process of the fiber-sintered stainless steel metal filter through which the raw material was passed after melt extrusion was a mesh sheet made of titanium. When the obtained biaxially oriented polyester film was used as a magnetic tape, coarse protrusions whose nuclei were titanium particles were detected, and running durability was deteriorated.
[0076] [Table 1]
Claims
1. A biaxially oriented polyester film for magnetic recording media, on surface A on which a magnetic layer is formed, has 0 to 1 protrusions per 1000 m that are greater than 0.5 μm in height from a reference plane as analyzed using a shape analysis laser microscope measurement with inorganic particles having a melting point of 1600° C. or more as nuclei. 2 A biaxially oriented polyester film.
2. 2. The biaxially oriented polyester film according to claim 1, wherein the surface A has a surface average roughness SRaA of 0.5 nm or more and 5 nm or less, and the other surface B of the surface A has a surface average roughness SRaB of 5 nm or more and 12 nm or less.
3. 2. The biaxially oriented polyester film according to claim 1, which is composed of at least two layers, a layer A forming the surface A and a layer B forming the other surface.
4. 2. The biaxially oriented polyester film according to claim 1, wherein the total thickness is from 3 μm to 5 μm.
5. 2. The biaxially oriented polyester film according to claim 1, wherein the polyester constituting the biaxially oriented polyester film is a polymer having polyethylene terephthalate or ethylene-2,6-naphthalenedicarboxylate as a main repeating unit.
Citation Information
Patent Citations
Magnetic recording medium and method of manufacturing the same
JP2010049731A
Support for magnetic recording medium and data storage using the same
JP2010250910A
Biaxially oriented laminated polyester film and data storage
JP2016192247A
Biaxially oriented polyester film
JP2020164807A
Polyester film for magnetic recording medium, polyester film roll for magnetic recording medium, magnetic recording medium, and magnetic recording medium roll
JP2021111431A